pH-Responsive Amphoteric p (APTMACl-co-AMPS) Hydrogel as Effective Multiple Dye Sponge Network From Aqueous Media - Demirci, Sahin; Ari, Betul; Aktas, Nahit; Sahiner, Nurettin (Frontiers in Materials, 2022)
Here, the cationic poly (3-acrylamidepropyl trimethyl ammonium chloride) [p (APTMACl)], anionic poly (2-acrylamido-2methylpropane sulfonic acid) [p (AMPS)], and amphoteric poly (APTMACl-co-AMPS) hydrogels were prepared via free-radical polymerization techniques as pH-sensitive hydrogels. The prepared systems were used in methylene blue (MB), and Eosin Y (EY) removal from aqueous media. HCl-treated p (APTMACl-co-AMPS) hydrogels prepared in 1:3 mol ratio adsorbed higher amount of MB and EY from their corresponding 50 ml 50 ppm aqueous solutions that are 47.5 ± 0.9, and 10.7 ± 0.1 mg/g, respectively. Also, the adsorbed amount of MB and EY by HCl-treated p (APTMACl-co-AMPS) hydrogels decreased with the increase in the medium pH from 3.0 to 9.0. It was also observed that HCl-treated p (APTMACl-co-AMPS)-3 hydrogels removed 39.2 ± 0.2, and 28.1 ± 1.0 mg/g MB and EY dyes simultaneously from their corresponding 50 ml 50 ppm aqueous mixture solutions. MB and EY adsorption by HCl-treated p (APTMACl-co-AMPS)-3 hydrogels were found to abide by pseudo-first-order adsorption kinetics. Moreover, MB adsorption by HCl-treated p (APTMACl-co-AMPS) hydrogels were found to fit with Freundlich, EY adsorption fit with Langmuir isotherms. The distribution coefficient values of HCl-treated p (APTMACl-co-AMPS) hydrogels were calculated as 3.7 ± 0.1 and 1.3 ± 0.1 for MB and EY, respectively. The calculated selectivity coefficient value showed that HCl-treated p (APTMACl-co-AMPS) hydrogels are at least 3-fold higher selective to MB than EY.